Sodium Thiosulfate (Hydrogen Sulfide Donor): Ameliorates the Pituitary-testicular Axis Dysfunction Induced by Cyclophosphamide and/or Ionizing Gamma Radiation in Albino Rats - Osman, Ahmed H. (B R Nahata Smriti Sansthan International Journal of Phramaceutical Sciences & Clinical Research, 2022)
Background: Hypothalamic-pituitary-testicular axis represents a complex biological structure organ regulating reproductive function. The present study aimed to investigate the potential protective effect of sodium thiosulfate (STS) as a hydrogen sulfide donor on the pathophysiological effects of cyclophosphamide (CYP) and/or ionizing gamma radiation (IR) on pituitary-gonadal axis through the improvement of pathological, biochemical, and hormonal alteration in male rats. Materials and Methods: Rats of experimental groups were received STS (400 mg/kg b.w. for 14 days, i.p.) before treatment with CYP and/or IR, except normal control rats received saline only.